Thermal evolution of an ancient subduction interface revealed by Lu–Hf garnet geochronology, Halilbagi Complex (Anatolia) - Pourteau, Amaury; Scherer, E.; Schorn, S.; Bast, R.; Schmidt, A.; Ebert, L. (Elsevier, 2018)
The thermal structure of subduction zones exerts a major influence on deep-seated mechanical and chemical processes controlling arc magmatism, seismicity, and global element cycles. Accretionary complexes exposed inland may comprise tectonic blocks with contrasting pressure–temperature (P–T) histories, making it possible to investigate the dynamics and thermal evolution of former subduction interfaces. With this aim, we present new Lu–Hf geochronological results for mafic rocks of the Halilbagi Complex (Anatolia) that evolved along different thermal gradients. Samples include a lawsonite–epidote blueschist, a lawsonite–epidote eclogite, and an epidote eclogite (all with counter-clockwise P–T paths), a prograde lawsonite blueschist with a “hairpin”-type P–T path, and a garnet amphibolite from the overlying sub-ophiolitic metamorphic sole. Equilibrium phase diagrams suggest that the garnet amphibolite formed at ~0.6–0.7 GPa and 800–850 °C, whereas the prograde lawsonite blueschist records burial from 2.1 GPa and 420 °C to 2.6 GPa and 520 °C. Well-defined Lu–Hf isochrons were obtained for the epidote eclogite (92.38 ± 0.22 Ma) and the lawsonite–epidote blueschist (90.19 ± 0.54 Ma), suggesting rapid garnet growth. The lawsonite–epidote eclogite (87.30 ± 0.39 Ma) and the prograde lawsonite blueschist (ca. 86 Ma) are younger, whereas the garnet amphibolite (104.5 ± 3.5 Ma) is older. Our data reveal a consistent trend of progressively decreasing geothermal gradient from granulite-facies conditions at ~104 Ma to the epidote-eclogite facies around 92 Ma, and the lawsonite blueschist–facies between 90 and 86 Ma. Three Lu–Hf garnet dates (between 92 and 87 Ma) weighted toward the growth of post-peak rims (as indicated by Lu distribution in garnet) suggest that the HP/LT rocks were exhumed continuously and not episodically. We infer that HP/LT metamorphic rocks within the Halilbagi Complex were subjected to continuous return flow, with “warm” rocks being exhumed during the tectonic burial of “cold” ones. Our results, combined with regional geological constraints, allow us to speculate that subduction started at a transform fault near a mid-oceanic spreading centre. Following its formation, this ancient subduction interface evolved thermally over more than 15 Myr, most likely as a result of heat dissipation rather than crustal underplating.